Form finding of assembled lattice structure considering the effect of joint stiffness. (June 2021) - Liu, Fengcheng; Feng, Ruoqiang; Daniel Tsavdaridis, Konstantinos
Abstracts: Joint stiffness can have a significant effect on the stability of single-layer lattice structure. However, it is yet unclear what is the degree of influence of joint stiffness on the form finding of assembled lattice structures. This paper presents a form finding method that suits assembled free-form single-layer lattice structures while the effect of joint stiffness on the form finding of the structure is investigated. Based on the experimental results of Ring-Sleeve joint, spring elements are initially used to simulate the joint stiffness and then finite element models of the assembled single-layer lattice structures with semi-rigid joints are established. The effect of joint stiffness on the structural form finding is studied by changing the spring stiffness. Thereafter, the optimal shapes of the assembled lattice structures with different joint stiffness and improved buckling load capacity are obtained. Finally, the mechanical properties of the resulted structures with different joint stiffness are extensively compared. The results show that different joint stiffness generate different structural shapes, and the greater joint stiffness results in higher structural height. Furthermore, both the structural buckling load capacity and the imperfection sensitivity increase with the increase of joint stiffness. Overall, the buckling load capacity of the semi-rigid model is lower than that of the replaced model that obtained based on the rigid structure.